"Values of Noble Character Education Reflected in the Creation of Syi'ir Mitra Sejati by Kh. Bisri Rembang" - Subaidi Masyhud (Jurnal Hikmatuna, 2018)
Abstract: This research explores the values of noble character education in Syi'ir Mitra Sejati, a work created by KH. Bisri Rembang. The study utilizes library research as the methodology and employs descriptive qualitative analysis to describe and analyze various phenomena, social activities, attitudes, beliefs, perceptions, and individual or group thinking. The primary data for this research is collected from the book Syi'ir Mitra Sejati. The data analysis method employed is descriptive analysis, which involves collecting, organizing, analyzing, and interpreting the data. The research focuses on exploring the moral values present in the text, specifically those related to character education. The findings reveal two significant values: the value of social responsibility and the value of appreciating achievements. The value of social responsibility reflects an attitude and action of willingly assisting others and the community in need. On the other hand, the value of appreciating achievements motivates individuals to create something beneficial for the community, as well as acknowledging and valuing the success of others. Additionally, the research highlights the importance of cultivating friendly and communicative attitudes, which involve expressing happiness when interacting with others, socializing, and cooperating. These values should be applied to both ourselves and students, enabling us to live harmoniously based on the religious doctrines we follow while fostering friendship. The communicative value is also evident in the intimacy and closeness observed within families and relations, as exemplified by KH. Bisri Rembang's efforts to propagate Islam in the style of Ahlusunnah Wal Jama'ah across various communities. Lastly, the research emphasizes the value of tolerance, which appreciates religious diversity, ethnic differences, opinions, and actions of others. This tolerant value fosters a sense of mutual respect among individuals of different religions, ethnicities, and backgrounds, contributing to the continuity of harmonious living.